1942
DOI: 10.5254/1.3546606
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between the Observed Density of Crystalline Rubber and the Density Calculated from X-Ray Data

Abstract: When unvulcanized rubber is stretched quickly, an orientation of structure occurs parallel to the direction of extension. This orientation is usually regarded as a form of crystallization, because of the optical and other phenomena which accompany it. It is also accompanied by a change of volume. When unstretched rubber is subjected to suitable temperatures below about 10° C, it too becomes crystalline. The crystallization of rubber is accompanied by an increase of density, and the simultaneous production of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1946
1946
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…The rates of crystallization observed in the present work are in reasonable agreement with observations of density by Bekkedahl [5] and Treloar [69] at 0 0 C, by Smith and Hanna [56] at -20 0 C, and by van Rossem and Lotichius [53] at 4 0 C and _10 0 C. Likewise, a similar rate can be calculated from observations of Young's modulus at 0 0 C made by Conant and Liska [16].…”
Section: Rate Of Crystallizationsupporting
confidence: 81%
See 1 more Smart Citation
“…The rates of crystallization observed in the present work are in reasonable agreement with observations of density by Bekkedahl [5] and Treloar [69] at 0 0 C, by Smith and Hanna [56] at -20 0 C, and by van Rossem and Lotichius [53] at 4 0 C and _10 0 C. Likewise, a similar rate can be calculated from observations of Young's modulus at 0 0 C made by Conant and Liska [16].…”
Section: Rate Of Crystallizationsupporting
confidence: 81%
“…Values for this quantity, calculated from measurements of density or specific gravity reported by previous workers [4,5,8,14,19,31,39,53,55,56,72] generally lie within the same limits, although a few are somewhat lower. Holt and McPherson [32] found a volume change of about 1.85 percent on stretching a specimen of vulcanized rubber to an elongation of 700 percent at 25 0 C. Treloar [69), by stretching unvulcanized rubber at 0 0 C, observed a volume decrease of over 3 percent, the highest value reported.…”
Section: Magnitude Of the Volume Change On Crystallizationmentioning
confidence: 87%
“…Moreover, density difference is expected to be not relevant for the calculations according to Equation (7). In the literature [77] it was reported that, in the case of NR, density value should be between that of amorphous and crystalline NR: these values range between 0.9 and 0.96. The variation of matrix density is below 6%, and this gives an uncertainty of the density of the composite even lower.…”
Section: Composites Based On Sp 2 Carbon Allotropesmentioning
confidence: 99%